As práticas discursivas argumentativas de alunos do ensino médio no laboratório didático de Física - Carlos Eduardo Porto Villani (2002)
In this research, we analyze the discursive dimension of science teaching and learning, through a study that emphasizes the role of language and of the pedagogical laboratory as mediators in this process. Therefore, we sought to investigate the argumentative discursive practices of secondary school students, which are brought about by an experimental activity in a didactic laboratory studying Physics, with the goal of understanding how they influence the construction and possession of knowledge. Through this research, we were able to identify the elements that compose students argumentative practices in the didactic laboratory. Such discursive is dynamic and depends intrinsically on the methods for association of objects of discourse exchange and the discourse elements: data (empirical, rescued or provided), tasks (techniques, strategies or analyses) and knowledge (scholastic or ordinary). The methods for association begin by taking a position and creating a consensus to be evaluated and serve as feedback to restart the dynamic. We obtained, as the main result of our investigation, a structure that characterizes the argumentative discourse practices of laboratory classes and shows its didactic dynamics. We also emphasize that the didactic laboratory fortifies the students discourse with a specific element: empirical data. This, when placed in the discourse, determines the possible ways of associating the objects of discourse exchange. We conclude that the argumentative game increases the likelihood of the students establishing relations between scientific knowledge and phenomena observed in the laboratory.